2014
DOI: 10.4103/2141-9248.138033
|View full text |Cite
|
Sign up to set email alerts
|

Clinical profile, maternal and fetal outcomes of acute hepatitis e in pregnancy

Abstract: Background:Pregnant women are at increased risk of complications in hepatitis E virus (HEV) infection, with the risk increasing as the pregnancy progresses, often leading to fulminant hepatic failure and adverse fetal outcome.Aims:The primary objective of the following study is to evaluate the maternal and fetal complications of this infection and secondary aim is to compare the clinical features of hepatitis E in pregnant women to those in non-pregnant women.Subjects and Methods:This was a hospital based case… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
21
0

Year Published

2015
2015
2025
2025

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(24 citation statements)
references
References 16 publications
3
21
0
Order By: Relevance
“…Shinde et al ( 12 ) reported in their 2-year prospective study that 46.1% of pregnant patients developed encephalopathy compared with 34% in the non-pregnant group. Among the pregnant women, 67.3% survived and 32% died.…”
Section: Discussionmentioning
confidence: 99%
“…Shinde et al ( 12 ) reported in their 2-year prospective study that 46.1% of pregnant patients developed encephalopathy compared with 34% in the non-pregnant group. Among the pregnant women, 67.3% survived and 32% died.…”
Section: Discussionmentioning
confidence: 99%
“…Excluding the low detection efficiency of RT-nested PCR, the transient existence of viremia [ 38 ] or low viral load [ 39 ] in these patients may be the main reasons. Additionally, studies have demonstrated that HEV infection in pregnant women can result in intrauterine growth restriction, abortions, still births or neonatal death [ 3 , 4 ]. In the present study, we did not observe any adverse effects on the pregnant and neonatal outcomes in the three pregnant women with new infections.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that a significant proportion of pregnant women with hepatitis E may progress to fulminant hepatitis during epidemics, especially in the third trimester, with a high mortality rate of 15–20 % [ 2 ]. On the other hand, although HEV is mainly transmitted by the fecal-oral route, epidemiological and clinical studies have suggested that vertical transmission of HEV may frequently happen in HEV infected pregnant women and lead to adverse fetal outcomes, such as miscarriage, stillbirth and neonatal death [ 3 , 4 ]. Moreover, although scarcely documented, the available data suggest secondary transmission of HEV may occur among family members both in outbreaks and sporadic infections [ 5 – 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…Pregnant women are at increased risk of complications in HEV infection, with the risk increasing as the pregnancy progresses, often leading to fulminant hepatic failure and death in a high number of cases. 92 Acute HEV infection is especially severe during second and third trimesters of pregnancy, and it may lead to fulminant hepatic failure and death in 30–100% of patients. 93 There is also increased number of obstetric complications, e.g., premature rupture of membranes, postpartum hemorrhage, spontaneous abortions, and intrauterine fetal death.…”
Section: Pregnancymentioning
confidence: 99%